Women Language Features in Tennessee Williams’ A Streetcar Named Desire - Iga Rahadiyanti (Vivid: Journal of Language and Literature, 2020)
The purpose of this study is to observe the types of women language features and the most frequent women language feature used by the main women characters in the dialogue of Tennessee Williams’ A Streetcar Named Desire play. Ten women language features proposed by Robin Lakoff is used to analyze the data. This study only observes eight out of ten women language features proposed by Robin Lakoff, namely tag question, intensifier, hypercorrect grammar, hedges or fillers, empty adjectives, precise color terms, super polite form, and avoidance of strong swear words. This study excludes emphatic stress and rising intonation on declaratives feature. Due to the absence of any numeric data, this study uses descriptive qualitative approach. The data is taken from written script of the play which consists of eleven scenes. Seven women language features found namely lexical hedges or fillers, tag question, intensifier, empty adjectives, superpolite form, avoidance of strong swear words, and precise color terms. The most frequent feature is lexical hedges or fillers (59.49%) while no hypercorrect grammar is found. This study supports Lakoff theory since most of the features are found in the conversation of main women characters